Credit Counselling in Canada: An Empirical Examination. Issue 1 (22nd July 2013) - Ben-Ishai, Stephanie; Schwartz, Saul
Abstract When debt becomes unmanageable, two options for a consumer debtor in Canada are: (1) enlisting the services of a bankruptcy trustee, and (2) becoming a client of a not-for-profit credit counselling agency. Each of these options is regulated differently and has public and private dimensions. At first glance, these two options might seem to illustrate the potential of multiple legal orders to better serve the public. In this paper, however, we argue, based on empirical research on the credit counselling industry, that while this pluralism has potential to facilitate debt relief in Canada, it has failed to do so. The lines between public and private options have been blurred to the point where they are difficult to discern, and the consumer debtor is ultimately disadvantaged.